2019
DOI: 10.1002/ange.201901405
|View full text |Cite
|
Sign up to set email alerts
|

Quaternization of Vinyl/Alkynyl Pyridine Enables Ultrafast Cysteine‐Selective Protein Modification and Charge Modulation

Abstract: Quaternized vinyl‐ and alkynyl‐pyridine reagents were shown to react in an ultrafast and selective manner with several cysteine‐tagged proteins at near‐stoichiometric quantities. We have demonstrated that this method can effectively create a homogenous antibody–drug conjugate that features a precise drug‐to‐antibody ratio of 2, which was stable in human plasma and retained its specificity towards Her2+ cells. Finally, the developed warhead introduces a +1 charge to the overall net charge of the protein, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Pyridinium salts constitute ap rivileged class of compounds of both natural and synthetic importance. [8] Over the last century,N -substituted pyridinium scaffolds have been used in organic chemistry as valuable synthetic intermediates or reagents, [9] oxidants, [10] ionic liquids, [11] phase-transfer catalysts, [12] as well as in material science [13] and biology [14] ( Figure 2). Thepyridinium core is also found in nature as part of secondary metabolites,f or example in marine sponges.…”
Section: Introductionmentioning
confidence: 99%
“…Pyridinium salts constitute ap rivileged class of compounds of both natural and synthetic importance. [8] Over the last century,N -substituted pyridinium scaffolds have been used in organic chemistry as valuable synthetic intermediates or reagents, [9] oxidants, [10] ionic liquids, [11] phase-transfer catalysts, [12] as well as in material science [13] and biology [14] ( Figure 2). Thepyridinium core is also found in nature as part of secondary metabolites,f or example in marine sponges.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in 2016, Bernardes et al reported the use of carbonylacrylic reagents for irreversible cysteine selective protein modification and have more recently described the use of quaternized pyridine salts for cysteine capture. 25,26 Recently, novel divinylpyrimidine linkers have also been developed for selective bioconjugation through re-bridging of reduced disulfide bonds in native antibodies. 27 In this study, we report our efforts towards the synthesis and evaluation of a series of novel heterocyclic warheads capable of cysteine capture.…”
Section: Introductionmentioning
confidence: 99%
“…First, we turned our attention to the pyridinium salt structural motif, which proved to be useful in many areas 18 such as molecular recognition, 19 catalysis, 20 and medicinal chemistry. 21 Gratifyingly, the treatment of diazocines 5a and 4b with MeI cleanly afforded salts 6a and 6b , respectively, without competitive opening of the oxygen bridge under the action of the strong alkylating agent. Moreover, the bisester function was used to surround the hydrophobic cavity of the V-shaped structure by hydrogen bond donors, useful in molecular recognition.…”
Section: Resultsmentioning
confidence: 99%